The perception of vegetables producers in relation to pest control in the community of Várzea Comprida dos Oliveiras Pombal–PB Brazil - Sousa, Luci Cleide Farias Soares; Sousa, José da Silva; Pereira, Emmanuel Moreira; Freires, Glauciene Ferreira; Maracaja, Patrício Borges (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
<!--[if gte mso 9]> 800x600 <![endif]-->Pest control in agriculture is usually done through pesticides, which also end up with beneficial organisms (predators, bees and other pollinators) in this context, the biological control appears as a technique that uses natural means, created to decrease the population of organisms considered pests. The control can be done by another organism (predator, parasite or pathogen) that attacks the pest and can be very efficient in controlling the main feature and not cause cumulative damage to crops or the natural enemies of the target control. This paper presents a survey of small producers of vegetables in Várzea Comprida dos Oliveiras, the municipality of Pombal - Paraíba, on the types of crops in the region, found major pest, pest control methods, and the perception that farmers have on control methods employed. The results show that some farmers do not use chemicals to control pests, but those who use them, show no knowledge of the risks in the management strengths of wrong, is not aware of the risks of health problems, but also show no awareness on the damage caused to the environment. There is a need to implement programs to raise awareness about the problems caused to health and the environment by chemicals, as well as a clarification of what is biological control and the importance of it to preserve the environment.<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";} --> <!--[endif] -->